Serum Levels of IL-35, One of the Newest Members of Interleukin-12 Family of Cytokines, in Patients with Vitiligo - Yıldız Hayran; Çiğdem Yücel; Esra Fırat Oğuz; Funda Eren; Turan Turhan; Başak Yalçın (Mattioli1885, 2024)
Introduction: Vitiligo is a chronic skin disorder in which immune dysregulation has been reported as one of the major etiopathological factors. Interleukin-12 (IL-12), IL-23 and IL-27 of IL-12 cytokine family were identified as critical cytokines in the pathogenesis of many autoimmune and inflammatory skin diseases including vitiligo. IL-35 is one of the newest member of IL-12 cytokine family. Objectives: The purpose of our study was to examine serum IL-35 levels in addition to serum IL-12, IL-23, IL-27 levels in the vitiligo patients and control group, and to investigate the relationship of these cytokines with the characteristics of vitiligo. Methods: Serum IL-12, IL-23, IL-27 and IL-35 levels of 78 vitiligo patients and 70 healthy volunteers were analyzed using the enzyme-linked immunosorbent assay (ELISA). We compared the IL-12 cytokine family levels in the patient and control groups, and investigated the relationship of these levels with the characteristics of vitiligo. Results:Patients had higher levels of IL-12 (31.2 versus 20.1, P < 0.001) and IL-35 (9.6 versus 8.1, P = 0.031). Patient and control groups had similar levels of IL-23 (P = 0.78) but were correlated with the Vitiligo Area Scoring Index (VASI) (P = 0.022, r = 0.35). Patients had lower levels of IL-27 (207.6 versus 258.7, P < 0.001). In addition, the levels of serum IL-27 were correlated negatively with the Vitiligo Disease Activity (VIDA), and positively with disease duration (P = 0.007, r = 0.30). Conclusions: Differences of serum levels between Vitiligo patients and healthy controls, significant relationships with the characteristics of vitiligo suggest that the IL-12 cytokine family may play a role in the pathogenesis of vitiligo.